2020
DOI: 10.1073/pnas.1912022117
|View full text |Cite
|
Sign up to set email alerts
|

Maternal activation of the EGFR prevents translocation of gut-residing pathogenic Escherichia coli in a model of late-onset neonatal sepsis

Abstract: Late-onset sepsis (LOS) is a highly consequential complication of preterm birth and is defined by a positive blood culture obtained after 72 h of age. The causative bacteria can be found in patients’ intestinal tracts days before dissemination, and cohort studies suggest reduced LOS risk in breastfed preterm infants through unknown mechanisms. Reduced concentrations of epidermal growth factor (EGF) of maternal origin within the intestinal tract of mice correlated to the translocation of a gut-resident human pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 51 publications
2
79
0
Order By: Relevance
“…Finally, Escherichia/Shigella counts had a relatively strong negative correlation with EGF levels. Previous studies have found that reduced concentrations of maternally derived EGF in mice correlated with E. coli gut translocation, and that supplementation with EGF protected the gut from colonization by enteropathogenic E. coli in a young rabbit model 50,51 . Perhaps EGF concentration could be important in ameliorating the effect of antibiotics on pathogen colonization in the preterm gut.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, Escherichia/Shigella counts had a relatively strong negative correlation with EGF levels. Previous studies have found that reduced concentrations of maternally derived EGF in mice correlated with E. coli gut translocation, and that supplementation with EGF protected the gut from colonization by enteropathogenic E. coli in a young rabbit model 50,51 . Perhaps EGF concentration could be important in ameliorating the effect of antibiotics on pathogen colonization in the preterm gut.…”
Section: Discussionmentioning
confidence: 94%
“…Because of lack of the intestinal epithelial barrier, the cultured dendritic cells were directly incubated in dextran-containing medium, which resulted in difficulty in observing the delivering of dextran from hESC-GCs into dendritic cells. Newberry and colleagues (5,(37)(38)(39)(40)(41)(42)(43) have demonstrated that acetylcholine induces GAP formation via mAChR4 expressed by intestinal GCs and that activation of EGFR in GCs can inhibit the GAP formation. hESC-GCs and hESC were found to express mAChR4 and EGFR, evidence by RT-qPCR, immunocytochemistry, and Western blotting (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that breast milk may be involved in determining the duration of the previously discussed window of opportunity. Additionally, milk-derived EGF has been attributed protective features by inhibiting the formation of GAPs during the early postnatal phase, which in turn prevents the translocation of gut bacteria and thus, systemic pathogen dissemination ( 210 ). Nevertheless, and as previously mentioned, the formation of GAPs must also happen during a precise time window before weaning to develop lifelong tolerance to the gut bacteria ( 142 ).…”
Section: The Importance Of Breast Milk For the Development Of The Neonatementioning
confidence: 99%